Correctors of ΔF508 CFTR restore global conformational maturation without thermally stabilizing the mutant protein. Issue 2 (26th October 2012) - He, Lihua; Kota, Pradeep; Aleksandrov, Andrei A.; Cui, Liying; Jensen, Tim; Dokholyan, Nikolay V.; Riordan, John R.
Abstract : Most cystic fibrosis is caused by the deletion of a single amino acid (F508) from CFTR and the resulting misfolding and destabilization of the protein. Compounds identified by high‐throughput screening to improve ΔF508 CFTR maturation have already entered clinical trials, and it is important to understand their mechanisms of action to further improve their efficacy. Here, we showed that several of these compounds, including the investigational drug VX‐809, caused a much greater increase (5‐ to 10‐fold) in maturation at 27 than at 37°C (<2‐fold), and the mature product remained short‐lived ( T 1/2 ~4.5 h) and thermally unstable, even though its overall conformational state was similar to wild type, as judged by resistance to proteolysis and interdomain cross‐linking. Consistent with its inability to restore thermodynamic stability, VX‐809 stimulated maturation 2–5‐fold beyond that caused by several different stabilizing modifications of NBD1 and the NBD1/CL4 interface. The compound also promoted maturation of several disease‐associated processing mutants on the CL4 side of this interface. Although these effects may reflect an interaction of VX‐809 with this interface, an interpretation supported by computational docking, it also rescued maturation of mutants in other cytoplasmic loops, either by allosteric effects or via additional sites of action. In addition to revealing the capabilities and some of the limitations of this important investigational drug, these findings clearly demonstrate that ΔF508 CFTR can be completely assembled and evade cellular quality control systems, while remaining thermodynamically unstable.—He, L., Kota, P., Aleksandrov, A. A., Cui, L., Jensen, T., Dokholyan, N. V., Riordan, J. R. Correctors of ΔF508 CFTR restore global conformational maturation without thermally stabilizing the mutant protein. FASEB J. 27, 536–545 (2013). www.fasebj.org